The asymptotic stability of xn+1-a2xn-1+bxn-k=0 - Piyapong Niamsup (2018)
We give the necessary and sufficient conditions for the asymptotic stability of the linear delay difference equation xn+1-a2xn-1+bxn-k= 0, n=0, 1, ..., where a and b are arbitrary real numbers and k is a positive integer greater than 1. The obtained conditions are given in terms of parameters a and b of difference equations. The method of proof is based on arithematic of complex numbers as well as properties of analytic functions.